Hubungan antara Pengetahuan dengan Perilaku dalam Pencegahan Penularan COVID-19 pada Pegawai di Salah Satu Kantor Pemerintah Daerah Kabupaten Sumedang - Vania Salsabila; Nuzirwan Acang; Budiman (Bandung Conference Series: Medical Science, 2022)
Abstract. Coronavirus disease 2019 (COVID-19) is still a major health problem in the world, including in Indonesia. The government continues to make various efforts to suppress the COVID-19 case. One of which is regulation in the workplace as well as that carried out by the Regional Government of Sumedang Regency. The implementation of these policies must be supported by knowledge about COVID-19 and good behavior towards COVID-19 from every employee. This study aims to determine the relationship between knowledge and behavior in preventing the transmission of COVID-19 to employees at one of the Regional Government Offices of Sumedang Regency. This study uses an analytic observational method with a quantitative approach and a cross-sectional study design. Data analysis used in the form of univariate analysis to distribute the frequency distribution of each variable and bivariate analysis to find the relationship between knowledge and behavior using Fisher's Exact Test. Data collection was carried out in August 2021 using a google form questionnaire adapted from WHO training materials that had been tested for validity and reliability to 72 employees at the Regional Financial and Asset Management Agency of Sumedang Regency. Most of the respondents had good knowledge of COVID-19, namely 52 people (72.2%) and moderate behavior towards COVID-19, namely 42 people (58.3%). This study uses a significance level of 0.05. Fisher's Exact Test showed a p-value of <0.001, meaning that there was a significant relationship between knowledge about COVID-19 and behavior towards COVID-19 among employees at the Regional Financial and Asset Management Agency of Sumedang Regency. Knowledge will affect the way a person behaves in everyday life. Knowledge of a disease can change a person's behavior in dealing with a disease. Abstrak. Coronavirus disease 2019 (COVID-19) masih menjadi masalah kesehatan utama dunia termasuk di Indonesia. Pemerintah terus melakukan berbagai upaya untuk menekan kasus COVID-19 salah satunya pengaturan di tempat kerja begitupun juga yang dilakuan Pemerintah Daerah Kabupaten Sumedang. Penerapan kebijakan tersebut harus didukung dengan pengetahuan tentang COVID-19 dan perilaku terhadap COVID-19 yang baik dari setiap pegawai. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan dengan perilaku dalam pencegahan penularan COVID-19 pada pegawai di salah satu kantor Pemerintah Daerah Kabupaten Sumedang. Penelitian ini menggunanakan metode observasional analitik dengan pendekatan kuantitatif dan rancangan studi cross-sectional. Analisis data yang digunakan berupa analisis univariat untuk mempresentasikan distribusi frekuensi setiap variabel serta analisis bivariat untuk mencari hubungan antara pengetahuan dengan perilaku menggunakan Fisher’s Exact Test. Pengambilan data dilakukan pada bulan Agustus 2021 dengan menggunakan kuesioner google form yang diadaptasi dari WHO training material yang sudah di uji validitas dan reliabilitas kepada 72 pegawai di Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Sumedang. Sebagian besar responden memiliki pengetahuan tentang COVID-19 yang baik yaitu sebanyak 52 orang (72,2%) dan perilaku terhadap COVID-19 yang sedang yaitu sebanyak 42 orang (58,3%). Penelitian ini menggunakan tingkat signifikansi α=0,05. Fisher’s Exact Test menunjukkan nilai p sebesar <0,001, artinya terdapat hubungan yang signifikan antara pengetahuan tentang COVID-19 dengan perilaku terhadap COVID-19 pada pegawai di Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Sumedang. Pengetahuan akan memengaruhi cara seseorang berperilaku dalam kehidupan sehari-hari. Pengetahuan atas suatu penyakit dapat mengubah perilaku seseorang dalam menghadapi suatu penyakit.